Teaching English in Non-Linguistic faculties using Innovative Techniques - Khamrayeva Shahlo Shuxratovna (International Journal on Orange Technologies, 2021)
This article is about teaching English in non-linguistic universities through multimedia apps. It also discusses some features of the topic and some teaching techniques are given like an example